ChemInform Abstract: Regioselective Syntheses of 2, 7‐(Het)arylpyrido[2, 3‐d]pyrimidines by an Orthogonal Cross‐Coupling Strategy. Issue 7 (22nd February 2013) - Maingot, Lucie; Dehbi, Oussama; Buron, Frederic; Aadil, Mina; Akssira, Mohamed; Routier, Sylvain; Guillaumet, Gerald
Abstract Two sequential cross‐coupling reactions of substrate (I) with arylboronic acids allow the approach to the desired target compounds.